COMPARISON OF EXPERIMENTAL STUDIES AND NUMERICAL MODELING RESULTS OF CONCRETE FILLED TUBULAR ELEMENTS WITH DEMOUNTABLE JOINTS - Semko P. О. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article presents the results of experimental tests of compressed tubular elements with demountable joints investigated on the central and noncentral compression (with eccentricities 0, 0,25 and 0.5 from the diameter of the sample) and numerical simulation by the finite element method. The obtained results were compared for similar samples and their models. For which using numerical simulation in the Femap software system a stress-strain state was investigated and graphical representations of principal stresses were presented. For comparison the tensions that arose when the shell’s steel pipe was reached the yield strength were selected. The mean square deviation and the coefficient of variation of the data obtained varied in the range of 5 – 7%, which indicates the correspondence of the results and allows further research of partial replacement of experimental tests with numerical simulation